2014
DOI: 10.3389/fphys.2014.00040
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions in C. elegans

Abstract: As in other multicellular organisms, the nematode Caenorhabditis elegans uses gap junctions to provide direct cell-to-cell contact. The nematode gap junctions are formed by innexins (invertebrate analogs of the connexins); a family of proteins that surprisingly share no primary sequence homology, but do share structural and functional similarity with connexins. The model organism C. elegans contains 25 innexin genes and innexins are found in virtually all cell types and tissues. Additionally, many innexins hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…This led to some extrapolation in the literature that innexin channels may also contain hexameric hemichannels and dodecameric junction channels like connexin [29][30][31][32]. On the other hand, it has also been reported that invertebrate gap junction channels are larger than vertebrate junction channels [12][13][14][15]20].…”
Section: Discussionmentioning
confidence: 94%
“…This led to some extrapolation in the literature that innexin channels may also contain hexameric hemichannels and dodecameric junction channels like connexin [29][30][31][32]. On the other hand, it has also been reported that invertebrate gap junction channels are larger than vertebrate junction channels [12][13][14][15]20].…”
Section: Discussionmentioning
confidence: 94%
“…Although Cxs and Inxs share similar membrane topology and form similar intercellular structures their sequences are unrelated (Phelan, ; Oshima et al, ). To date, mammalian genomes encode approximately twenty Cx‐encoding genes whereas C. elegans and D. melanogaster genomes encode twenty five and eight Inx‐encoding genes, respectively (Phelan and Starich, ; Söhl et al, ; Simonsen et al, ). Currently, at least five Cxs (Cx30.2, Cx36, Cx45, Cx50, Cx57) are definitively known to be expressed within mammalian neurons, while five others (Cx29, Cx30, Cx32, Cx43, Cx47) are expressed exclusively in glia (Nagy et al, )—at least in mature circuits.…”
Section: What Makes An Electrical Synapse?mentioning
confidence: 99%
“…Currently, at least five Cxs (Cx30.2, Cx36, Cx45, Cx50, Cx57) are definitively known to be expressed within mammalian neurons, while five others (Cx29, Cx30, Cx32, Cx43, Cx47) are expressed exclusively in glia (Nagy et al, )—at least in mature circuits. Similarly, only a subset of Inxs are known to be expressed in invertebrate neurons (Simonsen et al, ). This diversity of Cx/Inx genes provides ample opportunity for complex GJ formation where each hemi‐channel could be created from multiple Cx/Inxs (heteromeric) or hemi‐channels created by different Cx/Inxs could couple between cells (heterotypic, discussed below).…”
Section: What Makes An Electrical Synapse?mentioning
confidence: 99%
“…Innexins in invertebrates are considered to have similar topology and functional properties to those of connexins and pannexins in vertebrates (Barbe, Monyer, & Bruzzone, ; Beyer, & Berthoud, ; Phelan & Starich, ; Simonsen, Moerman, & Naus, ). Connexins and innexins are known to form gap junctions by docking of hemichannels in adjacent cells and implicated in exchange of ions and small signaling molecules between cells (Phelan, ; Söhl, Maxeiner, & Willecke, ).…”
Section: Introductionmentioning
confidence: 99%